Ag nanoparticles-polypyrrole-carbon black/mesoporous TiO2 novel nanocomposite as ultrafast visible-light-driven photocatalyst. Issue 12 (15th June 2022) - Faisal, M.; Ahmed, Jahir; Rashed, Md.A.; Alsareii, S.A.; Harraz, Farid A.
Abstract: Effective design and fabrication of novel visible light-oriented photocatalysts is an existing challenging task that requires further dedicated efforts, and it has been always a main concern among the scientific community. This study deals with the design and fabrication of an extremely active and ultrafast ternary photocatalyst based on Ag nanoparticles, polypyrrole doped carbon black (PPy-C) and mesoporous TiO2 (m-TiO2 ). Sol-gel methodology along with sonication and photodeposition routes have been employed for the successful creation of the ternary framework. Ternary photocatalyst composed of uniform spherical titania nanoparticles (10–15 nm in size) perfectly intermingled with the polymeric linkage of PPy-C. Fruitful creation of unique trio photocatalyst between AgNPs, PPy-C and m-TiO2 was confirmed by XPS and XRD. FTIR analysis further supports the development of nanocomposite photocatalyst. TEM analysis showed uniform spherical m-TiO2 nanoparticles (10–15 nm in size) covered by PPy-C with compact nodes like appearance interlocked very well among each other. The newly developed Ag@PPy-C/m-TiO2 ternary photocatalyst exhibited band gap energy in desired visible range of spectra. The photocatalytic efficiency for all created photocatalysts has been evaluated taking Imidacloprid (insecticide derivative) and methylene blue (MB) dye as target pollutants. The novel Ag@PPy-C/m-TiO2 photocatalyst produced astonishing results with ultrafast removal of both Imidacloprid as well MB dye under visible light irradiation. The newly created ultrafast Ag@PPy-C/m-TiO2 photocatalyst has removed 96.0% of the insecticide Imidacloprid in only 25 min with almost ⁓ 2.65 times more efficient than bare m-TiO2 towards the removal of insecticide derivative. The present report offers a highly encouraging and vastly talented Ag@PPy-C/m-TiO2 ternary photocatalyst, enabling the ideal management of extremely lethal and notorious chemicals.